Exploring the Thermodynamic Limits of Enhanced H2 Recovery With Inherent Carbon Removal From Low Value Aqueous Biomass Oxygenate Precursors - Ochonma, Prince; Blaudeau, Claire; Krasnoff, Rosalie; Gadikota, Greeshma (Frontiers in Energy Research, 2021)
Rational integration of chemical pathways at the molecular scale to direct thermodynamically favorable enhanced H2 production with inherent carbon removal from low-value substrates can be guided by exploring the thermodynamic limits of feasibility. The substrates of interest are biomass oxygenates that are water-soluble and uneconomical for separation from water. In this study, we investigate the thermodynamic feasibility of recovering H2 with inherent carbon removal from biomass oxygenates such as ethanol, methanol, glycerol, ethylene glycol, acetone, and acetic acid. The influence of biomass oxygenate-to-water ratios, reaction temperature of 150°C – 325°C, and CaO or Ca(OH)2 as the alkalinity source on the yields of H2, CH4, CO2 and Ca-carbonate are investigated. By maintaining the fluids in the aqueous phase under pressure, energy needs associated with vaporization are circumvented. The hypothesis that enhanced alkalinity favors the preferential formation of CO (precursor for CO2 formation) over CH4 and aids the formation of calcium carbonate is investigated. The findings from these studies inform the feasibility, design of experiments and the tuning of reaction conditions for enhanced H2 recovery with inherent carbon removal from biomass oxygenate sources.